Optimization of T6 heat-treated Al₂O₃-CNT reinforced aluminium composite: Microstructural and mechanical properties analysis - Salleh, Mohd Shukor; Abd Rahim, Mohammad Na’aim; Wakhi Anuar, Nur Farah Bazilah; Yahaya, Saifudin Hafiz; Al-Zubaidi, Salah Salman (Microscopy Society of Malaysia, 2025)
Metal matrix composites (MMCs) are widely used because of their high strength-to-weight ratios, excellent wear resistance, and thermal conductivity. Numerous studies have explored optimizing the mechanical properties of MMCs using hybrid nanoparticle reinforcements. In this study, alumina (Al₂O₃) and carbon nanotubes (CNTs) were used to reinforce aluminium alloy A356 through electromagnetic stirring (EMS), followed by T6 heat treatment. The composite fabrication involved varying Al₂O₃-CNT compositions and stirring durations. Optimization was conducted using the Taguchi Method to obtain the optimum combination of Al₂O₃-CNT. The influence of hybrid reinforcements and EMS on the microstructural distribution and mechanical properties was analyzed. Optical microscopy (OM) revealed that Al₂O₃-CNT reinforcement refined the grains and caused notable changes from dendritic to rosette structures, leading to closely packed grains with reduced porosity. Intermetallic phases in the composite were characterized using Field Emission Scanning Electron Microscopy (FESEM) and X-ray Diffraction (XRD). The results revealed that the composite with 0.5 wt.% CNTs, 6 wt.% Al₂O₃, and 10 minutes of stirring time produced higher mechanical properties compared to other parameters. Underthese conditions, yield strength, ultimate tensile strength, and elongation to fracture increased from 94.09 MPa, 221.10 MPa, and 11.37% to 117.18 MPa, 288.08 MPa, and 14.5%, respectively, after T6 heat treatment. These findings suggest that optimized reinforcement parameters, combined with T6 treatment, can significantly enhance the mechanical performance of Al₂O₃-CNT hybrid-reinforced aluminium alloys, making them promising materials for high-performance applications.